2014
DOI: 10.1097/igc.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Atl

Abstract: The SUVmax on FDG-PET/CT is useful for differentiating ovarian cancer from borderline or benign tumor with a high specificity and positive predictive value. However, our data also demonstrated a lower FDG uptake value in clear cell or mucinous histological finding, suggesting that SUVmax may vary depending on the tumor histological subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…MRI, measurement of tumor markers (such as SCC and CA19-9) [15], and FDG-PET [16] may be useful for differentiating benign MCT from malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…MRI, measurement of tumor markers (such as SCC and CA19-9) [15], and FDG-PET [16] may be useful for differentiating benign MCT from malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…PET studies were performed with a PET scanner (SET-3000BCT/L; Shimadzu, Kyoto, Japan) with an axial resolution of 3.9 mm and a 20 cm field of view, as described in our previous study (8). At the time of the tracer injection, all patients had fasted for at least 5 h and had blood glucose levels <150 mg/dl.…”
Section: Fdg-pet/ct and Imaging Analysismentioning
confidence: 99%
“…18 F-fluoro-2-deoxy-D-glucose-positron emission tomography (FDG-PET) with computed tomography (CT) is a well-established imaging modality for diagnosing and staging numerous types of cancer. In gynecological malignancies, previous studies revealed that the maximum standardized uptake value (SUV max ), a quantitative measurement of the tissue deoxyglucose metabolic rate measured on FDG-PET/CT, may be a useful parameter, not only for evaluating malignancy, but also for assessing the prognosis of patients with ovarian (7,8) and cervical cancer (9,10). In endometrial neoplasms, several previous reports demonstrated the usefulness of SUV max for preoperative risk stratification (11,12), although its prognostic impact remains controversial (13)(14)(15)(16), and it remains to be sufficiently studied in patients with uterine carcinosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography studies were performed with a PET scanner (SET-3000BCT/L; Shimadzu, Kyoto, Japan) with an axial resolution of 3.9 mm and a 20-cm field of view, as described in our previous study (12). At the time of the tracer injection, all the patients had fasted for ≥5 h and had blood glucose levels <150 mg/dl.…”
Section: Fdg-pet/ct and Imaging Analysismentioning
confidence: 99%
“…Previous studies have shown that the maximum standardized uptake value (SUV max ), a semiquantitative simplified measurement of the tissue deoxyglucose metabolic rate measured on FDG-PET/CT, could be a parameter for evaluating malignancy and for assessing the prognosis of patients with ovarian cancer (11,12) and endometrial cancer (13)(14)(15). Therefore, the use of SUV max as a new biomarker that is easily measureable on PET/CT prior to the start of treatment in patients with gynecological malignancies has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%